2013
DOI: 10.17761/ijyt.23.2.r8735770101m8277
|View full text |Cite
|
Sign up to set email alerts
|

iRest Yoga-Nidra on the College Campus: Changes in Stress, Depression, Worry, and Mindfulness

Abstract: Objectives: There is evidence that yoga practice is associated with decreased stress, worry, and depression, and with improved mindfulness-based skills. These findings had not been previously replicated for a sample of college students. This study evaluated whether iRest yoga-nidra practice was associated with reduced perceived stress, worry, and depression, and increased mindfulness in a sample of college student s. Methods: Sixty-six students age 18-56 completed an 8-week iRest yoga-nidra intervention that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 22 publications
1
48
0
1
Order By: Relevance
“…Studies were carried out in Australia, 8 , 29 India, 10 , 17 , 18 , 28 Iran, 7 , 16 Italy, 26 Taiwan, 22 the United Kingdom, 21 and the United States. 9 , 11 15 , 19 , 20 , 23 25 , 27 Studies focused on the meditative aspects of yoga while others incorporated exercise and/or gentle and slow movements and awareness. Types of yoga included Antenatal , 21 Anusara , 22 combination of Asana and Pranayama , 10 , 18 , 23 Hatha , 8 , 13 , 19 , 20 integrated yoga , 17 , 28 Iyengar , 14 Kirtan Kr iya, 15 , 26 Mindfulness-based meditation (with yoga), 9 , 11 , 27 Tai chi (with yoga), 12 unspecified, 7 , 16 and Viniyoga.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies were carried out in Australia, 8 , 29 India, 10 , 17 , 18 , 28 Iran, 7 , 16 Italy, 26 Taiwan, 22 the United Kingdom, 21 and the United States. 9 , 11 15 , 19 , 20 , 23 25 , 27 Studies focused on the meditative aspects of yoga while others incorporated exercise and/or gentle and slow movements and awareness. Types of yoga included Antenatal , 21 Anusara , 22 combination of Asana and Pranayama , 10 , 18 , 23 Hatha , 8 , 13 , 19 , 20 integrated yoga , 17 , 28 Iyengar , 14 Kirtan Kr iya, 15 , 26 Mindfulness-based meditation (with yoga), 9 , 11 , 27 Tai chi (with yoga), 12 unspecified, 7 , 16 and Viniyoga.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the studies reported that the participants were age 18 and older. 8 , 9 , 13 , 19 23 , 29 Other studies reported that participants were between the ages of 18 and 45, 12 , 17 , 23 , 24 18 and 60, 10 , 11 , 16 , 18 , 26 , 27 18 and 80, 14 20 and 35, 7 , 17 20 and 70, 22 , 26 30 and 70, 28 and 45 and 90. 15 Participants in the studies included pregnant women, 9 , 12 , 17 , 19 , 21 , 23 , 25 individuals with a depression diagnosis, 13 , 16 , 20 , 29 cancer patients, 22 , 28 narcotic drug addicts, 7 patients with poststroke hemiparesis, 8 patients with lower back pain, 10 college students, 11 patients with atrial fibrillation, 14 caregivers, 15 , 18 postpartum women, 24 anxiety, 26 and low-income pa...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yoga interventions for ER have demonstrated feasibility in a variety of settings, including a small number of studies conducted with young adults [ 76 , 77 , 78 , 79 ]. Based on these and other studies, Khanna and Greeson [ 80 ] noted that “the skills, insights, and self-awareness learned through yoga and mindfulness practice can target multiple psychological, neural, physiological, and behavioral processes implicated in addiction and relapse.…”
Section: Yoga To Improve Er and Reduce Aod Use/misusementioning
confidence: 99%